2015
DOI: 10.1007/s12687-015-0226-4
|View full text |Cite
|
Sign up to set email alerts
|

SCA2 predictive testing in Cuba: challenging concepts and protocol evolution

Abstract: Spinocerebellar ataxia type 2 (SCA2) is a neurodegenerative disease caused by a CAG repeat expansion in the ATXN2 gene. Cuba has the highest prevalence (6.57 cases/10 5 inhabitants) of SCA2 in the world. The existence of 753 affected individuals and 7173 relatives at risk prompted the development in 2001 of the first predictive testing program in the country. The medical records of over 1193 individuals, who requested the test within a 13-year period, were analyzed retrospectively. The presymptomatic and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Early diagnosis and treatment for genetic late‐onset neurodegenerative diseases could improve the quality of life for the mutation carriers and their families. The principal advantages lie mainly in knowing the actual risk of the disease over time and the physical and psychological preparation to cope with the disease . Additional benefits could result from the active interventions received sooner than is usually the case for manifest disease .…”
Section: Ethical Implications Of Predictive Testing and Early Intervementioning
confidence: 99%
See 2 more Smart Citations
“…Early diagnosis and treatment for genetic late‐onset neurodegenerative diseases could improve the quality of life for the mutation carriers and their families. The principal advantages lie mainly in knowing the actual risk of the disease over time and the physical and psychological preparation to cope with the disease . Additional benefits could result from the active interventions received sooner than is usually the case for manifest disease .…”
Section: Ethical Implications Of Predictive Testing and Early Intervementioning
confidence: 99%
“…For SCA2, the main ethical dilemmas relating to the predictive genetic testing are the request of a diagnosis test by an at‐risk adolescent and the de facto predictive testing of minors resulting from the no‐interruption of the pregnancy by couples with a test‐positive fetus. Last, there is the question of the elevated frequency of the ATXN2 gene large normal and intermediate alleles, which are able to expand into full penetrance range under certain conditions or could be associated with other neurodegenerative disorders, such as amyotrophic lateral sclerosis …”
Section: Ethical Implications Of Predictive Testing and Early Intervementioning
confidence: 99%
See 1 more Smart Citation
“…For many patients, the decision is not to test, which is why pre-test counseling and informed decision-making are critical. Initially it was thought that the demand for testing would be high, but studies on the uptake of predictive genetic testing for Huntington disease (Bernhardt et al, 2009; Creighton et al, 2003; Morrison et al, 2011; Panas et al, 2011; Tassicker et al, 2009) and other hereditary neurogenetic conditions (Cruz-Marino et al, 2013; Cruz-Marino et al, 2015; Riedijk et al, 2009) found that the majority of at-risk individuals decide not to learn their carrier status.…”
Section: Predictive Genetic Testingmentioning
confidence: 99%
“…Globally, the highest number of people with SCA live in Cuba (6.57 cases/10(5) inhabitants) and in the Azores Island [5,6]. Globally, SCA1, SCA2, SCA3, SCA6 and SCA7 represent the highest numbers of cases [1].…”
Section: Introductionmentioning
confidence: 99%